UiTM Law Newsletter : Vying for Visibility (Sept - Dis 2019) - UiTM Shah Alam, Faculty of Law (Faculty of Law, 2019)
A cordial welcome to the third issue of UiTMLaw eNewsletter. Visibility has become an integral part of higher education's continuous change process - and is increasingly becoming the centre of that change. Within that spirit, we feature members of the faculty's national and international engagements in communicating the value of our institution and its programmes to a global audience. We take enormous pride in our leading excellence to drive significant new growth and visibility of the faculty. As we vie for visibility, we highlight the endeavours of building UiTMLaw's research and publication reputation. The second half of 2019 has witnessed the faculty ascending to the apex especially in terms of publications in high impact factor Scopus peer reviewed international journals, national flagship journals and book publications. In line with our effort to achieve greater prominence, the Legal Insider column is making its maiden appearance in UiTMLaw eNewsletter by showcasing leading expertise of UiTMLaw. Our warmest appreciation to all colleagues, staff, students, alumni, partners and friends for your continuous support in making 2019 an amazing year for UiTMLaw. We are eternally grateful for without your commitment and encouragement, our achievements would not have been possible. Year 2020 is an exciting time for UiTMLaw as we continue to serve our mission of reinventing legal education for a diverse, complex world. We are hoping for everyone's renewed commitment and support in unleashing more potential and shaping the future to become a globally renowned university.